Enhancing endogenous adenosine A2A receptor signaling induces slow-wave sleep without affecting body temperature and cardiovascular function. (January 2019) - Korkutata, Mustafa; Saitoh, Tsuyoshi; Cherasse, Yoan; Ioka, Shuji; Duo, Feng; Qin, Rujie; Murakoshi, Nobuyuki; Fujii, Shinya; Zhou, Xuzhao; Sugiyama, Fumihiro; Chen, Jiang-Fan; Kumagai, Hidetoshi; et al.
Abstract: Insomnia is one of the most common sleep problems with an estimated prevalence of 10%–15% in the general population. Although adenosine A2A receptor (A2A R) agonists strongly induce sleep, their cardiovascular effects preclude their use in treating sleep disorders. Enhancing endogenous A2A R signaling, however, may be an alternative strategy for treating insomnia, because adenosine levels in the brain accumulate during wakefulness. In the present study, we found that 3, 4-difluoro-2-((2-fluoro-4-iodophenyl)amino)benzoic acid, denoted A2A R positive allosteric modulator (PAM)-1, enhanced adenosine signaling at the A2A R and induced slow wave sleep (SWS) without affecting body temperature in wild-type male mice after intraperitoneal administration, whereas the SWS-inducing effect of this benzoic acid derivative was abolished in A2A R KO mice. In contrast to the A2A R agonist CGS 21680, the A2A R PAM-1 did not affect blood pressure or heart rate. These findings indicate that enhancing A2A R signaling promotes SWS without cardiovascular effects. Therefore, small molecules that allosterically modulate A2A Rs could help people with insomnia to fall asleep. Graphical abstract: Image 1 Highlights: First positive allosteric modulator for adenosine A2A receptors, denoted A2A R PAM-1. A2A R PAM-1 promotes slow-wave sleep (SWS) in a dose-dependent manner in mice. Adenosine A2A receptors are necessary for A2A R PAM-1 to induce SWS. Enhancing adenosine A2A receptor signaling does not induce hypothermia. Systemic administration of A2A R PAM-1 does not affect blood pressure or heart rate.